Екстракт вівса як технологічний засіб підвищення якості м’яса гусей - Майборода, Данііл Олександрович; Майборода, Даниил Александрович; Maiboroda, Daniil; Данченко, Олена Олександрівна; Данченко, Елена Александровна; Danchenko, Olena; Здоровцева, Любов Миколаївна; Здоровцева, Любовь Николаевна; Zdorovtseva, Liubov; Федорко, А. С.; Данченко, Микола Миколайович; Данченко, Николай Николаевич; et al. (ТДАТУ, 2020)
Метою роботи було з‘ясування впливу екстракту вівса посівного в раціоні гусей на якість отриманого м‘яса та особливості його окисного псування при низькотемпературному зберіганні. Забій гусей проводили у 60-добовому віці. Після забою тушки гусей заморожували і надалі зберігали при температурі -18ºС відповідно до вимог ДСТУ (210 діб). Встановлено, що м‘ясо гусей, які отримували екстракт (дослідний зразок) відрізнялось вірогідно вищим умістом незамінних жирних кислот після забою. Додавання екстракту вівса до раціону гусей сприяло подовженню терміну вихідної стабілізації процесів пероксидного окиснення в отриманому м‘ясі. Активізація пероксидного окиснення у дослідному зразку розпочалась місяцем пізніше і наприкінці досліду за вмістом продуктів пероксидного окиснення дослідний зразок поступався контрольному на 28,6 %. У м‘ясі дослідного зразка вміст незамінних жирних кислот зберігався на вірогідно вищому рівні упродовж 120 діб. Целью работы было установление влияния экстракта овса посевного в рационе гусей на качество полученного мяса и особенности его окислительной порчи при низкотемпературном хранении. Убой гусей проводили в 60-суточном возрасте. После забоя тушки гусей замораживали и хранили при температуре -18ºС в соответствии с ГСТУ (210 суток). Установлено, что мясо гусей, получавших экстракт (опытный образец), отличалось достоверно высшим содержанием незаменимых жирных кислот после забоя. Добавление экстракта овса в рацион гусей способствовало продлению периода исходной стабилизации процессов пероксидного окисления в полученном мясе. Активизация окислительных процессов в опытном образце началась месяцем позже и в конце опыта по содержанию продуктов пероксидного окисления опытный образец уступал контрольному на 28,6%. В мясе опытного образца содержание незаменимых жирных кислот сохранялось на достоверно высшем уровне в течение 120 суток. The purpose of the work was to find out the effect of oat extract of Legarth geese in the diet of geese on the quality of the obtained meat and peculiarities of its oxidative spoilage at low temperature storage. Meat geese of two samples were used for the studies. The meat of the control sample was obtained from geese of the control group, which were kept in a standard diet balanced with all the nutrients and vitamins as recommended. Meat of the test sample was obtained from geese of the experimental group, which were added to the diet from the 10th to the 50th day with oat sowing extract. The caterpillars were slaughtered at the age of 60 days. After slaughter, the carcasses of geese were frozen and further stored at -18ºC according to the requirements of SSDU (210 days). Meat quality was determined by the content of lipoproxidation end products and fatty acid lipid composition. The results of the experiment proved that the meat obtained after slaughter of the geese of both samples was characterized by a low content of the final products of peroxide oxidation, but for the experimental sample this indicator was 83,8% higher than the corresponding control. The specificity of the dynamics of lipoperoxidation products in the control and experimental samples of meat during low-temperature storage is the duration of the initial period of the prooxidantantioxidant equilibrium, which is characterized by the low content of these compounds. The addition of oat extract to the diet of geese contributed to the prolongation of the initial stabilization of the prooxidant-antioxidant equilibrium for the meat of geese of the test sample. Activation of peroxide oxidation in the test sample began one month later and at the end of the experiment the content of the peroxide oxidation products gave the test sample 28,6% control. The meat of the prototype after slaughter was distinguished by a reliably high content of oleic and all essential fatty acids. On the 120th day, a significantly higher content of linoleic, arachidonic and docosahexaenoic acids was found in the experimental sample. After 210 days of storage, a prototype sample of goose meat in terms of the content of all irreplaceable fatty acids, except for arachidonic, did not exceed the control.
Экстракт овса как технологическое средство повышения качества мяса гусей
Oat extract as a technological means for improving the quality of geese meat
Keywords: м'ясо гусей; екстракт вівса; продукти ліпопероксидації; незамінні жирні кислоти; низькотемпературне зберігання; окисне псування; мясо гусей; экстракт овса; продукты липопероксидации; незаменимые жирные кислоты; низкотемпературное хранение; окислительная порча; goose meat; oat extract; lipoperoxidation products; essential fatty acids; low temperature storage; oxidative deterioration